Exploration of the perceptions of emergency physicians and interns regarding the medical documentation practices of interns. (21st July 2013) - Isoardi, Jonathon; Spencer, Lyndall; Sinnott, Michael; Nicholls, Kim; O'Connor, Angela; Jones, Fleur
Abstract: Objectives: The primary objective of the present study was to learn the factors that influence the documentation practices of ED interns. A second objective was to identify the expectations of emergency physicians (EPs) towards the medical record documentation of ED interns. Methods: A qualitative design was adopted using semi‐structured interviews in convenience samples drawn from both groups. Results: Eighteen interviews were conducted with intern volunteers and 10 with EP volunteers. One (5%) intern and two (20%) EPs had received medical documentation training. Factors that encouraged interns' documentation included: patient acuity (the more critical the condition, the more comprehensive the documentation) and the support of senior colleagues. Inhibiting factors included uncertainty about how much to write, and the shift being worked (interns indicated they wrote less at night). Factors of consequence to senior personnel included the apparent reluctance of interns to document management plans. They noted that interns frequently confine their notes to assessment, investigations and treatments, whereas EPs preferred records that demonstrated intern thought processes and included such matters as future actions to follow immediate treatment. A positive theme that emerged included the high level of support interns received from their senior colleagues. Another theme, the influence of patient acuity, held both positive and negative implications for intern writing practices. Conclusion: The lack of formal training is an impediment to the production of useful medical records by ED interns. One solution proposed by both interns and senior personnel was the introduction of the subject into intern education programmes.